Digital-Native News in South America Building Bridges with Diverse Audiences in Argentina, Brazil and Colombia - de Macedo Higgins Joyce, Vanessa (Palgrave Studies in Journalism and the Global South, 2024)
XII, 145 p. 6 illus.